Karekteristik Dan Uji Pembakaran Biopelet Campuran Cangkang Kelapa Sawit dan Serbuk Kayu Sebagai Bahan Bakar Alternatif Terbarukan - Muhammad Gifani Al Qadry; Danang Dwi Saputro; Rahmat Doni Widodo (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2023)
Non renewable energy it’s limited in capacity, when the energy runs out it cannot be renewed. Then it needs renewable energy to solve this problem. Biopellet is one of the renewable energy alternatives from biomass. The purpose of this research to identify characteristics and quality of biopellet a mixture palm kernel shell and sawdust. Method that used in this research is experiment. The compositions of a mixture that used in experiment is 100% : 30%, 70% : 30%, 50% : 50%, and 30% : 70%. The manufacture of biopellet used a 80 mesh of dust with the pressure of 200??/??2. The result of the test showed moisture content 7.6 – 11 %, volatile matter 67.6 – 68.08 %, ash content 1.53 – 2.57 %, carbon bonded 19.38 – 22.23 %, calorific value 3563.05 – 4366.73 kal/g, and density 1.03 – 1.32 g/cc. The best quality of biopellet is biopelet Bwith percentage 70 % palm kernel shell and 30 % sawdust. Biopellet B is the best quality of biopellet with 23 minute burn out